KUALITAS PELAYANAN BRAILLE E-TICKET AND EXTRAORDINARY ACCESS FOR VISUAL DISABILITIES (BREXIT) UNTUK REHABILITASI SOSIAL BINA NETRA OLEH UPT PUSKESMAS JANTI KOTA MALANG - Muhammad Reyhan Mumtaz Chaq; Eva Hany Fanida (Universitas Negeri Surabaya, 2022)
Quality and quality public services and excellent public services cannot be separated from the awareness of the government and the community to improve the quality of public services. Service quality is an effort to meet customer needs in an appropriate manner so that customer needs can be met (Dewi, 2016). Brexit or Braille E-Ticket and Extraordinary Access for Visual Disabilities is a public service innovation for people with visual impairments at UPT Puskesmas Janti, Malang City. This study uses qualitative research methods with data obtained from observations and interviews. This study analyzes service quality based on the theory of Kotler and Keller (2016) which includes the following five dimensions; dimensions of tangibles, reliability, responsiveness, assurance and empathy. The results showed that the Quality of Service of Braille E-Ticket and Extraordinary Access for Visual Disabilities (Brexit) for Blind Social Rehabilitation by UPT Puskesmas Janti Malang City has really tried to provide the best service according to the wishes of patients with visual impairments so that blind patients are loyal. and believe in using Brexit services and other services at the Janti Health Center. Keyword: Service Quality, Brexit, Blind Social Rehabilitation